(untitled) (XXI Century. Spanish Literature and Culture, 2003)
The author shows the more provincial and ‘patriotic’ side of Delibes related to his strong roots in his homeland: Valladolid and Castile. These settings become the stage for the author’s works, with the exception of his favorite Los Santos Inocentes, which is placed in country house in Extremadura. The author also highlights the reiteration of key themes in the plots of his novels.